Factors Associated with Visceral Leishmaniasis in the Americas: A Systematic Review and Meta-Analysis - Belo, Vinícius Silva (2013)
Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sergio Arouca. Departamento de Endemias Samuel Pessoa. Rio de Janeiro, RJ, Brasil.